PENGARUH INTENSITAS MENONTON VIDEO YOUTUBE TERHADAP PERKEMBANGAN KOMUNIKASI INTERPERSONAL SISWA/I KELAS 4 & 5 DESA SUKANAGARA RW 01 CIKUPA KABUPATEN TANGERANG - Wulan febrianti; H. A. Y. G. Wibisono (Nusantara Hasana Berdikari, 2021)
The level of popularity of smartphones among children is inseparable from the characteristics of smartphones that are indeed attractive to children. The Youtube application is one of the things that can trigger children to use the smartphone. to determine the effect of the intensity of watching YouTube videos on the development of interpersonal communication of grade 4 and 5 students. This study uses descriptive analysis techniques and simple linear regression analysis techniques. The sampling technique used was Total Sampling as many as 103 respondents. based on the Linearity test with the value of Sig. Deviation from Linearity > 0.005 (0.778 > 0.05). simple linear regression value (sig 0.002 < 0.005). There is an influence between the intensity of watching YouTube videos on the development of interpersonal communication. The development of the respondent's interpersonal communication is still in a good category, parental supervision and policy making rules in the use of smartphones by the school or government can be done properly. Motivation/Background: communication development of school-age children is an important aspect in terms of children's growth and development, the intensity of using gadgets, especially the intensity of watching YouTube videos that are easily liked by school-age children, thus attracting researchers to conduct this research. Method: This research uses descriptive analysis technique and simple linear regression analysis technique. The sampling technique used was Total Sampling as many as 103 respondents. Results: based on the linearity test with the value of Sig. Deviation from Linearity > 0.005 (0.778 > 0.05). simple linear regression value (sig 0.002 < 0.005).